Challenges of Implementing Assessment in Islamic Education (PAI) Learning in Madrasah Ibtidaiyah: Policy and Practice Analysis - Nazwa, Siti; Latieva, Alghina; Sabila, Husnul; Fithratunnisa, Fithratunnisa; Zulkarnain, Ali Iskandar (Lembaga Yasin AlSys, 2026)
Assessment in Islamic Education at the elementary madrasah level requires a holistic approach that captures not only students’ cognitive achievement but also their affective and psychomotor development. This study analyzes the challenges of assessing Islamic Education (Pendidikan Agama Islam/PAI) learning at Madrasah Ibtidaiyah and proposes practical strategies to strengthen holistic evaluation. A qualitative descriptive design based on library research was employed, using secondary data from journal articles, books, and policy documents. Data were collected through document review and analyzed through evidence synthesis and triangulation across sources to examine assessment practices in the cognitive, affective, and psychomotor domains. The findings indicate a persistent imbalance in PAI assessment, with teachers tending to prioritize cognitive and written assessments because they are easier to administer, while affective and psychomotor dimensions remain under-assessed despite their central role in shaping students’ religious character. The main barriers include limited teacher competence in authentic assessment, insufficient practical instruments and rubrics, limited time for sustained observation, heavy administrative workloads, variable institutional support, cultural resistance, and gaps in policy guidance. The study recommends sustained practice-oriented teacher training and mentoring, the development of simple and context-sensitive affective and psychomotor rubrics, the use of portfolio-based assessment models, timetable adjustments to support routine observation, and low-cost technology such as mobile applications and video portfolios to streamline documentation. Policy support is also needed through exemplar instruments, quality-oriented monitoring, and implementation incentives. This study contributes to Islamic education assessment discourse by emphasizing that valid and meaningful PAI evaluation must reflect students’ moral and spiritual development as well as academic learning.